Validation of the 2012 Fukuoka Consensus Guideline for Intraductal Papillary Mucinous Neoplasm of the Pancreas From a Single Institution Experience. Issue 7 (August 2017) - Yu, Songfeng; Takasu, Naoki; Watanabe, Toshihiro; Fukumoto, Tsuyoshi; Okazaki, Shinji; Tezuka, Koji; Sugawara, Shuichiro; Hirai, Ichiro; Kimura, Wataru
Abstract : Objectives: The 2012 Fukuoka consensus guideline has stratified the risks of malignant intraductal papillary mucinous neoplasm (IPMN) of the pancreas into "high-risk stigmata" (HRS) and "worrisome feature" (WF). This study aimed to evaluate its clinical validity based on a single institution experience. Methods: Eighty-nine patients who underwent surgical resection with pathological diagnosis of IPMN were retrospectively studied. Results: High-risk stigmata was significantly correlated with the prevalence of malignant IPMN as compared with WF. The positive predictive values of HRS and WF were 66.7% and 35.7% for branch duct IPMN and 80% and 38.1% for main duct IPMN, respectively. Univariate analysis indicated that all the factors in HRS and WF had statistical significance. Whereas multivariate analysis revealed only enhanced solid component (odds ratio [OR], 50.01; P = 0.008), presence of mural nodule (OR, 73.83; P < 0.001) and lymphadenopathy (OR, 20.85; P = 0.03) were independent predictors. Scoring HRS and WF by different numbers of positive factors resulted in improved predictive value. The area under the curve of HRS score was significantly lower than that of WF or HRS + WF score (0.680 vs 0.900 or 0.902, respectively; P < 0.001). Conclusions: As supplementary to the 2012 Fukuoka guideline, we suggest that calculating scores of WF and HRS may have superior diagnostic accuracy in predicting malignant IPMN.